Atypical multiple system atrophy is a new subtype of frontotemporal lobar degeneration: frontotemporal lobar degeneration associated with α-synuclein - Aoki, Naoya (Acta Neuropathol, 2015)
Multiple system atrophy (MSA) is a sporadic neurodegenerative disease clinically characterized by cerebellar signs, parkinsonism, and autonomic dysfunction. Pathologically, MSA is an α-synucleinopathy affecting striatonigral and olivopontocerebellar systems, while neocortical and limbic involvement is usually minimal. In this study, we describe four patients with atypical MSA with clinical features consistent with frontotemporal dementia (FTD), including two with corticobasal syndrome, one with progressive non-fluent aphasia, and one with behavioral variant FTD. None had autonomic dysfunction. All had frontotemporal atrophy and severe limbic α-synuclein neuronal pathology. The neuronal inclusions were heterogeneous, but included Pick body-like inclusions. The latter were strongly associated with neuronal loss in the hippocampus and amygdala. Unlike typical Pick bodies, the neuronal inclusions were positive on Gallyas silver stain and negative on tau immunohistochemistry. In comparison to 34 typical MSA cases, atypical MSA had significantly more neuronal inclusions in anteromedial temporal lobe and limbic structures. While uncommon, our findings suggest that MSA may present clinically and pathologically as a frontotemporal lobar degeneration (FTLD). We suggest that this may represent a novel subtype of FTLD associated with α-synuclein (FTLD-synuclein).